The illusion of simple - Jones, Charles Forrest, 1952- (University of Iowa Press, 2022)
"In a dry Kansas riverbed, a troop of Girl Scouts finds a human hand. This discovery leads Billy Spire, the tough and broken sheriff of Ewing County, to confront the depths of his community. The racism, the dying economy, the lies and truths of friendship, and his own injured marriage. But like any town where people still breathe, there is also love and hope and the possibility of redemption. To flyover people, Ewing County appears nothing more than a handful of empty streets amid crop circles and the meandering, depleted Arkansas River. But the truth of this place - the interwoven lives and stories - is anything but simple"--